Relevance of epidemiological surveillance in travelers: an imported case of Leishmania tropica in Mexico - Edith Araceli Fernández-Figueroa; Sokani Sánchez-Montes; Haydee Miranda-Ortíz; Alfredo Mendoza-Vargas; Rocely Cervantes-Sarabia; Roberto Alejandro Cárdenas-Ovando; Adriana Ruiz-Remigio; Ingeborg Becker (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
ABSTRACT We report the case of a patient with cutaneous leishmaniasis who showed a rapidly progressing ulcerative lesion after traveling to multiple countries where different Leishmania species are endemic. Diagnosis of Leishmania tropica, an exotic species in Mexico was established by using serological and molecular tools.